O współpracy między studiami polonoznawczymi Uniwersytetu Śląskiego a polonistyką pekińską .......... 63 - Tambor, Agnieszka (70 lat polonistyki Pekińskiego Uniwersytetu Języków Obcych: Dziedzictwo, rozwój, innowacje, 2025)
POLISH STUDIES COOPERATION BETWEEN THE UNIVERSITY OF SILESIA IN KATOWICE AND BEIJING FOREIGN STUDIES UNIVERSITY The article presents the history, forms, and prospects of cooperation between the University of Silesia in Katowice (UŚ) and Beijing Foreign Studies University (BFSU). This partnership began in 2004 with a delegation from Beijing and has since encompassed a wide range of educational activities, student and staff exchanges, joint research projects, and co-authored publications. The text discusses language courses, participation in international programs (Erasmus+, NAWA), joint research on the reception of Polish literature in China, doctoral dissertations by BFSU graduates defended in Poland, as well as conferences and academic publications. The article highlights the importance of joint projects, academic friendships, and cultural exchange as the foundations for long-term cooperation, and outlines opportunities for further development in teaching, research, and academic mobility.